2014
DOI: 10.1016/j.numecd.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Long term weight maintenance after advice to consume low carbohydrate, higher protein diets – A systematic review and meta analysis

Abstract: The short term benefit of higher protein diets appears to persist to a small degree long term. Benefits are greater with better compliance to the diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
106
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 45 publications
10
106
0
7
Order By: Relevance
“…Diets with the highest protein content significantly produced the most favourable reductions from baseline in body weight (-0.79 kg) and resulted in an interesting mitigation of the loss in lean mass as compared to the reference standard diets. 54 Finally, a systematic review and meta-analysis published in 2014 55 analysed the long-term effects of increased protein intake on body weight and fat mass. The 32 identified studies compared dietary advice promoting high protein and low carbohydrate intake with control dietary patterns.…”
Section: Meta-analyses and Systematic Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diets with the highest protein content significantly produced the most favourable reductions from baseline in body weight (-0.79 kg) and resulted in an interesting mitigation of the loss in lean mass as compared to the reference standard diets. 54 Finally, a systematic review and meta-analysis published in 2014 55 analysed the long-term effects of increased protein intake on body weight and fat mass. The 32 identified studies compared dietary advice promoting high protein and low carbohydrate intake with control dietary patterns.…”
Section: Meta-analyses and Systematic Reviewsmentioning
confidence: 99%
“…The authors concluded that a minimum difference of 5% in daily intakes (higher protein and lower carbohydrate) promoted improved weight loss, and resulted in up to 1 kg less fat mass, even in the long term. 55 However, these researchers also point out the high dropout rates in these trials, and stress the importance of thorough follow-up and correct implementation of the dietary change advice. 55 Indeed, adherence to dietary recommendations, and improving success rates, are issues that also need attention in future studies.…”
Section: Meta-analyses and Systematic Reviewsmentioning
confidence: 99%
“…In recent years several review articles on low-carbohydrate diets in various respects has been published [90][91][92][93] . There are different conclusions in these articles about the advantages and disadvantages of low-carbohydrate diets, which may seem somewhat contradictory but it is essential to note that various types of low-carbohydrate diets with different macronutrient content are included in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Moreover, recently conducted meta-analyses of longterm trials show lasting effects after the cessation of active intervention. 8,9 Another meta-analysis has demonstrated benefits of a low glycaemic index diet among individuals with obesity. 10 We should also distinguish between high trial 'retention' and high 'dietary adherence' .…”
Section: Correspondencementioning
confidence: 99%